Morphology of Microfibrillated Cellulose from Primary Sludge - Iwan Risnasari; Fauzi Febrianto; Nyoman J Wistara; Sucahyo Sadiyo; Siti Nikmatin (Masyarakat Peneliti Kayu Indonesia, 2013)
Sewage sludge is the largest waste produced from the pulp and paper mill, consist of fibers (50-60%) and inorganic materials.The aim of this study was to obtain the microfibrillated cellulose of sludge through extraction and cellulose disintegration. The cellulose disintegration conducted by a combinations of the refining and ultrasonication treatment. The results showed that after extraction process the mass of C and O were increased. Conversely the mass of Al, Ca, Si and S were decreased. The mass of C and O was further increased after refining and ultrasonication treatment. The process of extraction on sludge could remove lignin, hemicellulose and inorganic materials to obtain more pure cellulose. Cellulose disintegration by a combination of the refining 30 times followed by ultrasonication for 120 min produced microfibrillated cellulose with diameter of 284 nm.Key words: extraction, microfibrillated cellulose, morphology, sludge